Idealism in Education. Tradition and the Present. Selected Approaches and Implications - Ryk, Andrzej (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The paper present selected approaches to ancient and modern idealistic thought and its ability to influence how we think about education. Idealism has evolved from systemic understanding and interpreting reality to more subjective forms where an idea is rooted within the subject, its consciousness or self-consciousness in the first place. It turns out that idealism understood in such a way can still inspire the way educational activities are viewed. This refers in particular to the following categories: subjectivity, individualism, cognition, understanding, surrounding world, experienced world, mutual infiltration of individuals and systems.